Method for preparing oxygen based on pressure swing adsorption

By using the gradual boosting method and silica sol to improve the preparation of zeolite adsorbents in the pressure-switching adsorption process, the problems of reduced oxygen purity and shortened adsorbent service life caused by rough pressure-changing are solved, and the long-term stability of high-purity oxygen preparation and adsorbent performance are achieved.

CN119873749APending Publication Date: 2025-04-25YANTAI BEACON MEDICAL TECH CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510379223.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-28
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

In the existing oxygen preparation process of pressure-switching adsorption, the rough pressure-up method leads to the destruction of the microporous structure of the adsorbent, the oxygen purity is reduced, and the service life of the adsorbent is shortened.

Method used

The gradual pressure boosting method is adopted, first let the adsorbent and impurities act initially under a lower pressure, and then slowly increase the pressure so that the adsorbent and nitrogen are in full contact, establish a good balance, and finally strengthen adsorption. At the same time, by mixing the silica sol with zeolite, a solid-state network structure of silica is formed, which enhances the hardness and wear resistance of the adsorbent.

Benefits of technology

Effectively reduce the amount of unadsorbed nitrogen, greatly improve the purity of oxygen, meet the industry needs with high purity requirements, and extend the service life of the adsorbent.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a method for preparing oxygen based on pressure swing adsorption, and relates to the technical field of oxygen preparation. Comprising the following steps: compressing air to obtain compressed air, condensing the compressed air, separating to remove water vapor and oil mist to obtain pretreated air, introducing the pretreated air into a device filled with a zeolite adsorbent, adsorbing nitrogen, and flowing out oxygen as a product gas, the adsorption process adopts a gradual pressure increasing mode. According to the invention, a gradual pressure increasing mode is adopted, an adsorbent and impurities are primarily acted under relatively low pressure, then the pressure is slowly increased, so that the adsorbent is in full contact with nitrogen, good balance is established, finally, adsorption is enhanced, unadsorbed nitrogen is effectively reduced, the oxygen purity is greatly improved, and the industrial requirements with high purity requirements are met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of oxygen preparation, and in particular to a method for preparing oxygen based on pressure swing adsorption. Background Art

[0002] Pressure swing adsorption (PSA) is a highly efficient and energy-saving gas separation technology that is widely used in the field of oxygen production. Gas separation is achieved by using the difference in the adsorption capacity of adsorbents for different gases at different pressures. Under higher pressures, the adsorbent has a stronger adsorption capacity for impurity gases such as nitrogen, but a weaker adsorption capacity for oxygen, thereby enriching oxygen; under lower pressures, the impurity gases such as nitrogen adsorbed by the adsorbent are desorbed, and the adsorbent is regenerated and can be recycled.

[0003] Zeolite adsorbent plays a key role in the process of preparing oxygen by pressure swing adsorption due to its unique properties. It has a uniform microporous structure and a strong selective adsorption capacity for nitrogen. The reason is that the polarizability of nitrogen molecules is large and they are easily induced by the electric field on the surface of zeolite. At the same time, its huge specific surface area provides a large number of adsorption sites, has a high adsorption capacity, and has good thermal and chemical stability, and can withstand the heat and chemical effects in pressure swing adsorption. However, the current process of preparing oxygen by pressure swing adsorption still has some key problems that need to be solved in the actual operation process. In terms of pressure control, the common boosting method in the prior art is relatively rough, the boosting rate has not been precisely controlled, and the pressure rises rapidly in a short time. This method greatly affects the adsorption effect of zeolite adsorbent on nitrogen. According to the principle of adsorption equilibrium, the pressure change should be maintained at an appropriate rate to ensure that the adsorbent and nitrogen fully interact. However, during rough pressurization, the gas diffusion and adsorption process in the adsorbent micropores cannot reach the optimal equilibrium state, resulting in some nitrogen not being effectively adsorbed and directly mixing into the product oxygen, causing the oxygen purity to be significantly reduced. This makes it difficult to meet the needs of industries such as medical and electronics that have strict requirements on oxygen purity.

[0004] In addition, the rapid change in pressure during the process of increasing and decreasing pressure will also lead to intensified collisions between zeolite adsorbent particles. Adsorbents are usually porous structures, and the micropores inside them are crucial to adsorption performance. Frequent and violent particle collisions will destroy the microporous structure of the adsorbent, causing the micropores to be blocked and the pore size to change. This not only reduces the adsorption capacity of the adsorbent for nitrogen, but also shortens the service life of the adsorbent. After long-term operation, the performance of the adsorbent is greatly attenuated and needs to be frequently replaced, which increases production costs and equipment maintenance workload. Summary of the invention

[0005] The object of the present invention is to provide a method for preparing oxygen based on pressure swing adsorption to solve the technical problems raised by the above background technology.

[0006] To achieve the above object, the present invention provides the following technical solutions: A method for preparing oxygen based on pressure swing adsorption comprises the following steps: S1. compressing the air to obtain compressed air; S2, condensing the compressed air, separating and removing water vapor and oil mist to obtain pre-treated air; S3. The pretreated air is introduced into a device filled with zeolite adsorbent to adsorb nitrogen, and oxygen is discharged as a product gas. The adsorption process adopts a gradually increasing pressure method.

[0007] Preferably, in step S1, the pressure of the compressed air is 0.6-0.8 MPa.

[0008] Preferably, in step S2, the condensation temperature is 5-10°C.

[0009] Preferably, in step S3, the gradual pressure increase method is to first adsorb the pretreated air at 0.6-0.8 MPa for 10-15 seconds, then increase the pressure to 1.0-1.2 MPa at a pressure increase rate of 0.005-0.008 MPa / s, and continue adsorbing for 100-150 seconds.

[0010] The prior art uses a rough and rapid pressure-increasing method. The rough and rapid pressure-increasing method easily breaks the original adsorption equilibrium between the adsorbent and nitrogen. According to the adsorption equilibrium principle, pressure increase is conducive to adsorption, but the rough and rapid pressure-increasing method may cause the adsorption process to deviate from the optimal equilibrium state, resulting in the adsorption amount of nitrogen by the adsorbent not reaching the optimal value. Some nitrogen may not be fully adsorbed and pass through the adsorption tower with the airflow, affecting the separation effect of nitrogen. Since the rough pressure-increasing method affects the adsorption effect of the adsorbent on nitrogen, more nitrogen cannot be effectively adsorbed and is mixed into the product gas, resulting in a decrease in the purity of the generated oxygen. The present invention adopts a progressive pressure-increasing method, first adsorbing at a relatively low pressure of 0.6-0.8MPa for 10-15s, allowing the adsorbent to initially react with the impurity gas in the air, laying the foundation for subsequent adsorption. Then, the pressure is slowly increased to 1.0-1.2MPa at a rate of 0.005-0.008MPa / s. During this process, the adsorbent has sufficient time to fully contact and adsorb nitrogen, allowing the nitrogen to diffuse and adsorb in the micropores of the adsorbent in an orderly manner, establishing a good adsorption balance and effectively reducing the amount of unabsorbed nitrogen. Finally, adsorption is continued at a pressure of 1.0-1.2MPa for 100-150s to further strengthen the adsorption of nitrogen and ensure the adsorption effect, thereby greatly improving the oxygen purity and meeting the needs of industries with strict requirements on oxygen purity, such as medical and electronics.

[0011] Preferably, in step S3, the method for preparing the zeolite adsorbent comprises the following steps: S31, pouring silica sol into deionized water, stirring evenly, then adding sodium carboxymethyl cellulose additive, and continuing to stir and mix evenly to obtain a silica gel solution; S32, adding zeolite powder to the silica gel solution, stirring and mixing evenly to obtain a mixture; S33, adding the mixed material into an extruder, performing extrusion molding, and drying to obtain a primary ecological adsorbent; S34, placing the primary ecological adsorbent in a muffle furnace for calcination, and then cooling to room temperature to obtain an adsorbent.

[0012] In the technical solution of the present invention, the zeolite adsorbent adsorbs nitrogen as the pressure increases, and then desorbs nitrogen as the pressure decreases, thereby achieving the regeneration of the zeolite adsorbent. However, in the process of frequent pressure increase and pressure reduction, the rapid change of pressure will lead to the intensification of the collision between the zeolite adsorbent particles, and the frequent and violent particle collisions will cause the zeolite adsorbent particles to break and the microporous structure of the adsorbent to be destroyed, which not only reduces the adsorption capacity of the adsorbent for nitrogen, but also shortens the service life of the adsorbent. In order to solve the technical problem, the present invention improves the zeolite adsorbent. Silica sol is a dispersion system of nano-scale silica particles in water or solvent, which has good fluidity and wettability. In the process of preparing the zeolite adsorbent, when the silica sol is mixed with the zeolite, the silica sol can evenly penetrate between the zeolite particles and the internal pores. Due to its nano-scale particle size, the silica sol can fill the tiny gaps between the zeolite particles and form a continuous film on the surface of the particles. The individual zeolite particles are tightly bonded together, which greatly enhances the binding force between the particles. During the high-temperature roasting stage, the silica sol undergoes chemical conversion. As the temperature rises, the water in the silica sol gradually evaporates, and the nano-scale silica particles begin to approach each other, fuse and transform into a solid network structure of silica. The silica transformed from the silica sol forms a strong chemical bond with the zeolite particles. The silica network not only increases the overall hardness of the adsorbent, but also the adsorbent bonded and transformed by the silica sol can better resist these external forces with its enhanced hardness and wear resistance, effectively reducing the breakage and wear of the particles, thereby maintaining the structural integrity and stability of the adsorbent, ensuring its long-term stable adsorption performance, maintaining its adsorption capacity and extending its service life.

[0013] Preferably, in step S31, the mass fraction of the silica sol solution is 25-40%.

[0014] Preferably, in step S32, the mass ratio of the zeolite powder to the silica sol is 1:0.2-0.6, and the mass fraction of the silica sol is 30%.

[0015] In the technical solution of the present invention, as mentioned above, the hardness of zeolite is enhanced by the solid network structure formed by silica, which can better resist these external forces and effectively reduce the breakage and wear of particles. The present invention has found through experiments that the surface of zeolite must be combined with a sufficient amount of silica to form a complete solid network structure, which can maximize the hardness of zeolite. Therefore, the present invention controls the mass ratio of zeolite powder to silica sol to be less than 1:0.2. However, the present invention team unexpectedly discovered that as the amount of silica sol added continued to increase, when the mass ratio of silica sol to zeolite powder was less than 1:0.6, the adsorption performance of zeolite adsorbent to nitrogen suddenly dropped significantly. When the mass ratio of silica sol to zeolite powder was greater than 1:0.6, the adsorption performance of zeolite adsorbent to nitrogen did not change much, which was not expected by the present invention team. This may be because as the amount of silica sol added increases, the excess silica sol causes the pore size of the zeolite to be blocked. When the amount of sol added exceeds a certain critical value, this influence increases significantly, the passage of nitrogen molecules into the zeolite is blocked, and the accessible adsorption sites are greatly reduced, causing the adsorption capacity of the adsorbent to drop sharply, which in turn seriously affects the separation effect of nitrogen in the process of preparing oxygen by pressure swing adsorption. Therefore, the present invention simultaneously controls the mass ratio of zeolite powder to silica sol to be 1:0.2-0.6.

[0016] Preferably, in step S33, the drying temperature is 70-80° C. and the drying time is 4-6 hours.

[0017] Preferably, in step S34, the calcination temperature is 500-600° C., and the calcination time is 2-4 hours.

[0018] Compared with the prior art, the present invention has the following beneficial effects: The gradual pressure increase method is adopted. First, the adsorbent and impurities are initially reacted at a relatively low pressure, and then the pressure is slowly increased to allow the adsorbent and nitrogen to fully contact and establish a good balance. Finally, the adsorption is strengthened to effectively reduce the unabsorbed nitrogen and greatly improve the oxygen purity to meet the needs of industries with high purity requirements. The adsorbent is prepared with silica sol, which can penetrate into the gaps between zeolite particles and pores, and form a solid silicon dioxide network structure after high-temperature calcination, which enhances the particle binding force and the hardness and wear resistance of the adsorbent, reduces particle breakage and wear, maintains the stability of the adsorbent structure, and ensures long-term adsorption performance; Controlling the mass ratio of zeolite powder to silica sol within a reasonable range can ensure that there is sufficient silicon dioxide to form a complete solid network structure to improve the hardness of the zeolite, while avoiding excessive clogging of the zeolite pores by silica sol, which would lead to a significant decrease in adsorption performance. This can enhance the hardness of the adsorbent while maintaining good adsorption performance. DETAILED DESCRIPTION

[0019] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the implementation rules described are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Example 1

[0020] A method for preparing oxygen based on pressure swing adsorption comprises the following steps: S1. Start the air compressor to suck in and compress ambient air. Through the pressure regulating valve, the pressure of the compressed air is stably controlled at 0.7MPa to obtain compressed air; S2. Pass the compressed air into the condenser, adjust the refrigerant flow of the condenser, and reduce the temperature of the compressed air to 8°C. The cooled compressed air enters the oil-water separator to remove water vapor and oil mist therein to obtain pre-treated air; S3, the pre-treated air is passed into the adsorption device filled with the prepared zeolite adsorbent, the pressure in the device is maintained at 0.7 MPa, and the pre-treated air is adsorbed at this pressure for 14 seconds. After that, the pressure in the device is slowly increased to 1.1 MPa at a pressure increase rate of 0.007 MPa / s, and the adsorption is continued for 140 seconds at this pressure. During this period, the unadsorbed oxygen flows out from the device outlet as product gas, which is collected and subsequently tested.

[0021] The preparation method of the zeolite adsorbent comprises the following steps: S31. Pour 100 mL of 30% silica sol into a container containing 300 mL of deionized water. Use a magnetic stirrer to stir at 300 r / min for 30 minutes to evenly disperse the silica sol in the deionized water. Add 1.5 g of sodium carboxymethyl cellulose additive to the above solution and continue stirring for 45 minutes to obtain a uniform silica gel solution. S32, slowly adding 4A zeolite powder to the silica gel solution, the mass ratio of 4A zeolite powder to silica sol is 1:0.5, using a mechanical stirrer, stirring at a speed of 300 r / min for 90 minutes to ensure that the zeolite powder and the silica gel solution are fully mixed to obtain a mixture; S33, transfer the mixture to the extruder hopper, adjust the extruder die to extrude cylindrical particles with a diameter of 5mm. Control the extruder screw speed at 25r / min to ensure the stability of the extrusion process, spread the extruded particles evenly on the tray, and put them into the drying oven. Set the drying oven temperature to 75℃ and the drying time to 5 hours to obtain the primary ecological adsorbent; S34, carefully transfer the primary ecological adsorbent to the muffle furnace and close the furnace door. Raise the furnace temperature to 550°C at a heating rate of 5°C / min. After reaching the target temperature, keep the temperature for 3 hours. After the insulation is completed, turn off the power supply of the muffle furnace and let the adsorbent cool naturally to room temperature in the furnace to obtain the final zeolite adsorbent. Example 2

[0022] A method for preparing oxygen based on pressure swing adsorption comprises the following steps: S1. Start the air compressor to suck in and compress ambient air. Through the pressure regulating valve, the pressure of the compressed air is stably controlled at 0.7MPa to obtain compressed air; S2. Pass the compressed air into the condenser, adjust the refrigerant flow of the condenser, and reduce the temperature of the compressed air to 6°C. The cooled compressed air enters the oil-water separator to remove water vapor and oil mist to obtain pre-treated air; S3, the pre-treated air is passed into the adsorption device filled with the prepared zeolite adsorbent, the pressure in the device is maintained at 0.7 MPa, and the pre-treated air is adsorbed at this pressure for 12 seconds. After that, the pressure in the device is slowly increased to 1.1 MPa at a pressure increase rate of 0.006 MPa / s, and the adsorption is continued for 120 seconds at this pressure. During this period, the unadsorbed oxygen flows out from the device outlet as product gas, which is collected and subsequently tested.

[0023] The preparation method of the zeolite adsorbent comprises the following steps: S31. Pour 100 mL of 30% silica sol into a container containing 300 mL of deionized water. Use a magnetic stirrer to stir at 300 r / min for 30 minutes to evenly disperse the silica sol in the deionized water. Add 1.5 g of sodium carboxymethyl cellulose additive to the above solution and continue stirring for 45 minutes to obtain a uniform silica gel solution. S32, slowly adding 4A zeolite powder to the silica gel solution, the mass ratio of 4A zeolite powder to silica sol being 1:0.3, using a mechanical stirrer, stirring at a speed of 300 r / min for 90 minutes to ensure that the zeolite powder and the silica gel solution are fully mixed to obtain a mixture; S33, transfer the mixture to the extruder hopper, adjust the extruder die to extrude cylindrical particles with a diameter of 5mm. Control the extruder screw speed at 25r / min to ensure the stability of the extrusion process, spread the extruded particles evenly on the tray, and put them into the drying oven. Set the drying oven temperature to 75℃ and the drying time to 5 hours to obtain the primary ecological adsorbent; S34, carefully transfer the primary ecological adsorbent to the muffle furnace and close the furnace door. Raise the furnace temperature to 550°C at a heating rate of 5°C / min. After reaching the target temperature, keep the temperature for 3 hours. After the insulation is completed, turn off the power supply of the muffle furnace and let the adsorbent cool naturally to room temperature in the furnace to obtain the final zeolite adsorbent. Example 3

[0024] A method for preparing oxygen based on pressure swing adsorption comprises the following steps: S1. Start the air compressor to suck in and compress ambient air. Through the pressure regulating valve, the pressure of the compressed air is stably controlled at 0.7MPa to obtain compressed air; S2. Pass the compressed air into the condenser, adjust the refrigerant flow of the condenser, and reduce the temperature of the compressed air to 7°C. The cooled compressed air enters the oil-water separator to remove water vapor and oil mist therein to obtain pre-treated air; S3, the pre-treated air is passed into the adsorption device filled with the prepared zeolite adsorbent, the pressure in the device is maintained at 0.7 MPa, and the pre-treated air is adsorbed at this pressure for 13 seconds. After that, the pressure in the device is slowly increased to 1.1 MPa at a pressure increase rate of 0.006 MPa / s, and the adsorption is continued for 130 seconds at this pressure. During this period, the unadsorbed oxygen flows out from the device outlet as product gas, which is collected and subsequently tested.

[0025] The preparation method of the zeolite adsorbent comprises the following steps: S31. Pour 100 mL of 30% silica sol into a container containing 300 mL of deionized water. Use a magnetic stirrer to stir at 300 r / min for 30 minutes to evenly disperse the silica sol in the deionized water. Add 1.5 g of sodium carboxymethyl cellulose additive to the above solution and continue stirring for 45 minutes to obtain a uniform silica gel solution. S32, slowly adding 4A zeolite powder to the silica gel solution, the mass ratio of 4A zeolite powder to silica sol is 1:0.4, using a mechanical stirrer, stirring at a speed of 300 r / min for 90 minutes to ensure that the zeolite powder and the silica gel solution are fully mixed to obtain a mixture; S33, transfer the mixture to the extruder hopper, adjust the extruder die to extrude cylindrical particles with a diameter of 5mm. Control the extruder screw speed at 25r / min to ensure the stability of the extrusion process, spread the extruded particles evenly on the tray, and put them into the drying oven. Set the drying oven temperature to 75℃ and the drying time to 5 hours to obtain the primary ecological adsorbent; S34, carefully transfer the primary ecological adsorbent to the muffle furnace and close the furnace door. Raise the furnace temperature to 550°C at a heating rate of 5°C / min. After reaching the target temperature, keep the temperature for 3 hours. After the insulation is completed, turn off the power supply of the muffle furnace and let the adsorbent cool naturally to room temperature in the furnace to obtain the final zeolite adsorbent. Example 4

[0026] A method for preparing oxygen based on pressure swing adsorption comprises the following steps: S1. Start the air compressor to suck in and compress ambient air. Through the pressure regulating valve, the pressure of the compressed air is stably controlled at 0.8MPa to obtain compressed air; S2. Pass the compressed air into the condenser, adjust the refrigerant flow of the condenser, and reduce the temperature of the compressed air to 10°C. The cooled compressed air enters the oil-water separator to remove water vapor and oil mist therein to obtain pre-treated air; S3, the pre-treated air is passed into the adsorption device filled with the prepared zeolite adsorbent, the pressure in the device is maintained at 0.8MPa, and the pre-treated air is adsorbed at this pressure for 15 seconds. After that, the pressure in the device is slowly increased to 1.2MPa at a pressure increase rate of 0.008MPa / s, and the adsorption is continued for 150 seconds at this pressure. During this period, the unadsorbed oxygen flows out from the device outlet as product gas, which is collected and subsequently tested.

[0027] The preparation method of the zeolite adsorbent comprises the following steps: S31. Pour 100 mL of 30% silica sol into a container containing 300 mL of deionized water. Use a magnetic stirrer to stir at 300 r / min for 30 minutes to evenly disperse the silica sol in the deionized water. Add 1.5 g of sodium carboxymethyl cellulose additive to the above solution and continue stirring for 45 minutes to obtain a uniform silica gel solution. S32, slowly adding 4A zeolite powder to the silica gel solution, the mass ratio of 4A zeolite powder to silica sol is 1:0.6, using a mechanical stirrer, stirring at a speed of 300r / min for 90 minutes to ensure that the zeolite powder and the silica gel solution are fully mixed to obtain a mixture; S33, transfer the mixture to the extruder hopper, adjust the extruder die to extrude cylindrical particles with a diameter of 5mm. Control the extruder screw speed at 25r / min to ensure the stability of the extrusion process, spread the extruded particles evenly on the tray, and put them into the drying oven. Set the drying oven temperature to 80℃ and the drying time to 6 hours to obtain the primary ecological adsorbent; S34, carefully transfer the nascent adsorbent to the muffle furnace and close the furnace door. Raise the furnace temperature to 600°C at a heating rate of 5°C / min. After reaching the target temperature, keep the temperature for 4 hours. After the insulation is completed, turn off the power supply of the muffle furnace and let the adsorbent cool naturally to room temperature in the furnace to obtain the final zeolite adsorbent. Example 5

[0028] A method for preparing oxygen based on pressure swing adsorption comprises the following steps: S1. Start the air compressor to suck in and compress ambient air. Through the pressure regulating valve, the pressure of the compressed air is stably controlled at 0.6MPa to obtain compressed air; S2. Pass the compressed air into the condenser, adjust the refrigerant flow of the condenser, and reduce the temperature of the compressed air to 5°C. The cooled compressed air enters the oil-water separator to remove water vapor and oil mist to obtain pre-treated air; S3, the pre-treated air is passed into the adsorption device filled with the prepared zeolite adsorbent, the pressure in the device is maintained at 0.6MPa, and the pre-treated air is adsorbed at this pressure for 10 seconds. After that, the pressure in the device is slowly increased to 1.0MPa at a pressure increase rate of 0.005MPa / s, and the adsorption is continued for 100 seconds at this pressure. During this period, the unadsorbed oxygen flows out from the device outlet as product gas, which is collected and subsequently tested.

[0029] The preparation method of the zeolite adsorbent comprises the following steps: S31. Pour 100 mL of 30% silica sol into a container containing 300 mL of deionized water. Use a magnetic stirrer to stir at 300 r / min for 30 minutes to evenly disperse the silica sol in the deionized water. Add 1.5 g of sodium carboxymethyl cellulose additive to the above solution and continue stirring for 45 minutes to obtain a uniform silica gel solution. S32, slowly adding 4A zeolite powder to the silica gel solution, the mass ratio of 4A zeolite powder to silica sol being 1:0.2, using a mechanical stirrer, stirring at a speed of 300 r / min for 90 minutes to ensure that the zeolite powder and the silica gel solution are fully mixed to obtain a mixture; S33, transfer the mixture to the extruder hopper, adjust the extruder die to extrude cylindrical particles with a diameter of 5mm. Control the extruder screw speed at 25r / min to ensure the stability of the extrusion process, spread the extruded particles evenly on the tray, and put them into the drying oven. Set the drying oven temperature to 70℃ and the drying time to 4 hours to obtain the primary ecological adsorbent; S34, carefully transfer the nascent adsorbent to the muffle furnace and close the furnace door. Raise the furnace temperature to 500°C at a heating rate of 5°C / min. After reaching the target temperature, keep the temperature for 2 hours. After the insulation is completed, turn off the power supply of the muffle furnace and let the adsorbent cool naturally to room temperature in the furnace to obtain the final zeolite adsorbent.

[0030] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that after the pre-treated air is passed into the adsorption device filled with the prepared zeolite adsorbent, the pressure is directly increased from 0.7 MPa to 1.1 MPa by a rough pressure-increasing method. The remaining operation steps are the same.

[0031] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that the zeolite adsorbent prepared in this example is replaced by a common zeolite adsorbent purchased from the market. The remaining steps are the same.

[0032] Comparative Example 3 The difference between Comparative Example 3 and Example 5 is that in the preparation process of the zeolite adsorbent, the mass ratio of 4A zeolite powder to silica sol is 1:0.1. The remaining operation steps are the same.

[0033] Comparative Example 4 The difference between Comparative Example 4 and Example 4 is that in the preparation process of the zeolite adsorbent, the mass ratio of 4A zeolite powder to silica sol is 1:0.7. The remaining operation steps are the same.

[0034] Comparative Example 5 The difference between Comparative Example 5 and Example 4 is that in the preparation process of the zeolite adsorbent, the mass ratio of 4A zeolite powder to silica sol is 1:0.8. The remaining operation steps are the same.

[0035] Performance Testing 1. Oxygen purity test: Oxygen purity is measured using a gas chromatograph. First, at the oxygen outlet of the pressure swing adsorption device, use a calibrated gas sampling bag or stainless steel sampling bottle to carefully collect oxygen samples to ensure that no outside air is mixed in. Next, use a standard gas of known purity to calibrate the gas chromatograph. After injecting the standard gas, a standard curve is constructed based on the instrument response signal to quantitatively analyze the content of each gas component in the sample. Subsequently, the collected oxygen sample is injected into the gas chromatograph through the injection port, and the carrier gas carries the sample to separate in the chromatographic column. Different gases flow out of the chromatographic column at different times due to differences in distribution coefficients and are captured by the detector. Finally, based on the retention time and peak area of ​​each gas peak, the oxygen and impurity gas content is calculated with the help of the standard curve, and the oxygen purity is calculated using the formula oxygen purity (%) = (oxygen peak area / total peak area) × 100%.

[0036] 2. Adsorbent adsorption capacity test: The nitrogen adsorption capacity of the adsorbent under pressure conditions is tested using a static volumetric adsorption instrument. First, accurately weigh 1g of the adsorbent sample, place it in a vacuum oven, and vacuum degas for 6 hours. Transfer the adsorbent sample to the sample tube of the adsorbent instrument, and use high-purity nitrogen to purge the system to remove the air in the system. Gradually increase the pressure of the adsorbent instrument to 0.5MPa to allow the adsorption to reach equilibrium. The adsorbent instrument measures the changes in system pressure and gas volume, and calculates the amount of nitrogen adsorbed by the adsorbent under this pressure based on the ideal gas state equation. Adsorption capacity (mg / g) = (mass of adsorbed nitrogen / mass of adsorbent) × 1000, where the mass of adsorbed nitrogen is calculated by m = (P × V × M) / (R × T) (m is the mass of adsorbed nitrogen (g), P is the adsorption equilibrium pressure (Pa), V is the volume of adsorbed nitrogen (L), M is the molar mass of nitrogen (28 g / mol), R is the gas constant (8.314 J / (mol・K)), and T is the adsorption temperature (K)).

[0037] 3. Adsorbent hardness test The hardness of the adsorbent is measured using a Mohs hardness tester. First, the adsorbent is processed into a cylinder to ensure that the test surface is flat and smooth, and the test surface is polished with sandpaper to remove surface impurities and defects. During the test, the standard minerals of the Mohs hardness tester are used to gently scratch the surface of the adsorbent sample, starting with the mineral with lower hardness. Carefully observe whether there are scratches on the surface of the adsorbent. If scratches are left, switch to a mineral with a lower hardness and continue scratching until the surface of the adsorbent is no longer scratched. At this point, the hardness of the standard mineral equivalent to the hardness of the adsorbent sample is the Mohs hardness of the adsorbent. In order to improve the accuracy of the test, multiple scratching tests are required at different locations of the adsorbent sample, and the average value is finally taken as the hardness value of the adsorbent.

[0038] 4. Nitrogen adsorption capacity test after multiple adsorption and desorption For the nitrogen adsorption capacity test after multiple adsorption and desorption, a certain mass of adsorbent sample is first placed in the pressure swing adsorption device, and 1000 cycles are performed according to the set pressure swing adsorption process, including the steps of pressure increase, adsorption, pressure reduction, and desorption. After completing the set number of cycles, the adsorbent sample is taken out of the pressure swing adsorption device, and then its adsorption capacity is tested according to the above adsorbent adsorption capacity test method. The experimental results are shown in Table 1.

[0039] Table 1

[0040]

[0041] By comparing Example 1 of the present invention with Comparative Example 1, it can be seen that the purity of oxygen prepared by the rough pressure-increasing method in Comparative Example 1 is significantly lower than that in Example 1. This proves that the gradual pressure-increasing method of the present invention can improve the purity of the prepared oxygen.

[0042] By comparing Example 1 of the present invention with Comparative Example 2, it can be seen that the hardness of the zeolite adsorbent of Comparative Example 2 and the adsorption capacity of the adsorbent after 1000 adsorption and desorption cycles are significantly lower than those of Example 1. This proves that the zeolite adsorbent prepared by the present invention has good hardness and can extend the service life of the adsorbent.

[0043] By comparing Example 5 of the present invention with Comparative Example 3, it can be seen that the hardness of the zeolite adsorbent prepared in Comparative Example 3 is slightly lower than that of the zeolite adsorbent prepared in Example 5. This is because the amount of silica sol used is insufficient, resulting in the inability to combine a sufficient amount of silicon dioxide on the surface of the zeolite to form a complete solid network structure, causing the hardness of the zeolite to decrease slightly.

[0044] By comparing Example 4 of the present invention with Comparative Examples 4 and 5, it can be found that the adsorption capacity of the zeolite adsorbent in Comparative Examples 4 and 5 is greatly reduced relative to that in Example 4. This may be because as the amount of silica sol added increases, the excess silica sol causes blockage of the zeolite pores. When the amount of sol added exceeds a certain critical value, this influence is greatly increased, the passage for nitrogen molecules to enter the interior of the zeolite is blocked, and the accessible adsorption sites are greatly reduced, causing a sharp drop in the adsorption capacity of the adsorbent for nitrogen, which in turn seriously affects the separation effect of nitrogen in the process of preparing oxygen by pressure swing adsorption.

[0045] Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments, or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing oxygen based on pressure swing adsorption, characterized in that: The following steps are involved: S1. compressing the air to obtain compressed air; S2, condensing the compressed air, separating and removing water vapor and oil mist to obtain pre-treated air; S3. The pretreated air is introduced into a device filled with zeolite adsorbent to adsorb nitrogen, and oxygen is discharged as a product gas. The adsorption process adopts a gradually increasing pressure method.

2. A method for preparing oxygen based on pressure swing adsorption according to claim 1, characterized in that: In the step S1, the pressure of the compressed air is 0.6-0.8 MPa.

3. The method for preparing oxygen based on pressure swing adsorption according to claim 1, characterized in that: In step S2, the condensation temperature is 5-10°C.

4. The method for preparing oxygen based on pressure swing adsorption according to claim 1, characterized in that: In step S3, the gradual pressure increase method is to first adsorb the pretreated air at 0.6-0.8 MPa for 10-15 seconds, then increase the pressure to 1.0-1.2 MPa at a pressure increase rate of 0.005-0.008 MPa / s, and continue adsorbing for 100-150 seconds.

5. The method for preparing oxygen based on pressure swing adsorption according to claim 1, characterized in that: In step S3, the method for preparing the zeolite adsorbent comprises the following steps: S31, pouring silica sol into deionized water, stirring evenly, then adding sodium carboxymethyl cellulose additive, and continuing to stir and mix evenly to obtain a silica gel solution; S32, adding zeolite powder to the silica gel solution, stirring and mixing evenly to obtain a mixture; S33, adding the mixed material into an extruder, performing extrusion molding, and drying to obtain a primary ecological adsorbent; S34, placing the primary ecological adsorbent in a muffle furnace for calcination, and then cooling to room temperature to obtain an adsorbent.

6. A method for preparing oxygen based on pressure swing adsorption according to claim 5, characterized in that: In the step S31, the mass fraction of the silica sol is 25-40%.

7. A method for preparing oxygen based on pressure swing adsorption according to claim 6, characterized in that: In the step S32, the mass ratio of the zeolite powder to the silica sol in the silica gel solution is 1:0.2-0.6, and the mass fraction of the silica sol is 30%.

8. The method for preparing oxygen based on pressure swing adsorption according to claim 5, characterized in that: In step S33, the drying temperature is 70-80°C and the drying time is 4-6 hours.

9. The method for preparing oxygen based on pressure swing adsorption according to claim 5, characterized in that: In the step S34, the calcination temperature is 500-600° C. and the calcination time is 2-4 hours.

Citation Information

Patent Citations

  • Method and device for preparing high-purity oxygen based on coupling separation technology

    CN112960650A

  • High-purity nitrogen recovery method

    CN113120918A

  • High -purity high -pressure pressure swing adsorption equipment of making nitrogen

    CN205164437U

  • Nitrogen selective zeolite adsorbent and nitrogen adsorptionprocess using the same

    JP1997075720A

  • Air separation processes using zeolite ITQ-55

    US20230182066A1